PERFORMANCE OF RABBIT URINE ON THE YIELD AND YIELD COMPONENT OF CUCUMBER - Okonji, C. J.; Ajayi, E. O; Obisesan, O. I.; Osundare, O. T.; Adetuyi, A. O. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
Organic farming is known to be the production system where synthetic fertilizers and pesticides are largely or completely avoided, it has been observed recently the rapid growth of the system in the last decades. An experiment was conducted at the Vegetable Research Farm of National Horticultural Research Institute, Ibadan, Oyo state to determine the influence of rabbit urine as organic fertilizer on the growth and yield of two varieties of cucumber. The experiment was laid out in a factorial arrangement fitted into a randomized complete block design replicated 3 times. The trial comprised of two cucumber varieties (Marketer and Poinsett), urine application as soil and foliar application, NPK and the control. The results showed significant influence of the treatments on growth and yield of cucumber also significant interaction was observed between varieties and treatments used on yield attributes and yield of cucumber. The application of rabbit urine into the soil and by foliar on marketer cucumber significantly had the highest fruit yield in both years.